Medial pivot vs posterior stabilized total knee arthroplasty designs: a gait analysis study - Nicola Bianchi; Andrea Facchini; Nicola Mondanell; Federico Sacchetti; Roberta Ghezzi; Marco Gesi; Rodolfo Capanna; Stefano Giannotti (Medicinski glasnik, 2020)
Aim: To compare a medial pivot (MP) total knee arthroplasty (TKA) with posterior stabilized (PS) TKA designs from a subjective, clinical and biomechanical point of view, in a single-centre, single-surgeon, case-control non-randomized trial. Methods: Sixteen patients were randomly picked up from case series into each group. Subjective outcome was assessed using the Forgotten Joint Score Questionnaire (FJSQ). Clinical evaluation included range of motion (ROM). All patients underwent gait analysis by a treadmill with force-measuring plaques and videorecording device; data were recorded for 30 seconds and included cadence, step length, stance time and walking speed. A blinded qualitative analysis of the pattern of gait was defined as biphasic or non-biphasic. Descriptive statistics for the continuous study variables and statistical significance were calculated for all parameters with independent-samples t-test and χ2 test to analyse difference in pattern of gait between groups. Results: Mean FJSQ in the MP group was 91.87 (CI 95%: 88.12- 95.46) and 75.31 (CI 95%: 67.97-81.56) in the PS group (p=0.029). Mean post-operative ROM was 117° (CI 95%: 113°-122°) in the MP group and 112° (CI 95%: 108°-117°) in the PS group (p=0.14). No statistical difference was found between groups regarding all gait analysis parameters which have been recorded. Conclusion: MP TKA design showed better subjective results using the FJSQ, but it did not improve significantly clinical and functional outcomes compared to PS TKA design, at a short-term follow-up.
Keywords: forgotten joint; mid-flexion instability; PROMs; subjective results; TKA